Resepsi KH. Maemon Zubair terhadap Tafsir Al-Jalalain dalam Ngaji Ahadan di Pondok Pesantren Al-Anwar, Sarang - Fuaddin, Achmad; Qudsy, Saifuddin Zuhri (SUHUF, 2024)
This research examines reinterpretations by Kiai Maemon Zubair in reading Tafsir al-Jalalain. Researchers overlook this area. This research explores Maemon’s reception in reading Tafsir al-Jalalain, the factors influencing Maemon’s reception, and its implications. This research is classified as qualitative research with a content analysis study using Stuart Hall’s reception analysis framework. The research results show that Maemon’s reception in reading Tafsir al-Jalalain can be categorized as a dominant-hegemonic, negotiated, and oppositional position. Tafsir al-Jalalain, namely: differences in geographic location between Maemon and the author of Tafsir al-Jalalain, differences in the reasoning of Maemon and the author as well as strengthening ideology. Maemon’s reception, which is not always in line with al-Jalalain’s text, proves that learning in Islamic boarding schools is not always textual and only fixates on classical texts.